Desain Inovatif Kaki Palsu Low Cost : Pendekatan Finite Element Analysis - Kumarajati, Dhananjaya Yama Hudha (Universitas PGRI Yogyakarta, 2023)
This research aims to develop an affordable, innovative prosthetic leg design using a Finite Element Analysis (FEA) approach. Lower limb loss is a serious problem for many individuals, and prosthetic limbs are becoming a common solution, but the high cost and lack of availability of effective designs are major obstacles. The research method involved a literature study on prosthetic limbs, prosthetic limb modeling, and FEA. In this research, we model the geometry of a prosthetic leg using 360 fusion, apply FEA to understand its mechanical behavior, and optimize the design based on the analysis results. FEA testing shows that the proposed prosthetic leg design is capable of withstanding a load of 1000N with a minimum safety factor of 3.64. The results of this research indicate that the resulting prosthetic leg design can be an effective and affordable solution for individuals in need, with the potential to improve quality of life and mobility.